First Comparison of Mesospheric Winds Measured with a Fabry-Perot - Wonseok Lee; Yong Ha Kim; Changsup Lee; Qian Wu (Korean Space Science Society (KSSS), 2018)
A Fabry-Perot interferometer (FPI) for mesospheric observations was installed at King Sejong Station (62.2°S, 58.9°W) in Antarctica in 2017. For the initial validation of the FPI measurements, we compare neutral wind data recorded with the FPI with those from a Meteor Radar (MR) located nearby. The overall characteristics of the FPI and MR winds of both OH 892.0 nm (87 km) and OI 557.7 nm (97 km) airglow layers are similar. The FPI winds of both layers generally match the MR winds well on the observed days, with a few exceptions. The correlation analysis of the FPI and MR wind data shows that the correlation coefficients for the zonal winds at 87 and 97 km are 0.28 and 0.54, respectively, and those for the meridional winds are 0.36 and 0.54, respectively. Based on the assumption that the distribution of the airglow emissions has a Gaussian function with respect to the altitude, we calculated the weighted mean winds from the MR wind profile and compared them with the FPI winds. By adjusting the peak height and full width at half maximum of the Gaussian function, we determined the change of the correlation between the two winds. The best correlation for the OH and OI airglow layers was obtained at a peak height of 88–89 km and 97–98 km, respectively.